The archaeal roots of eukaryotic life - Valerie De Anda; Kathryn E. Appler; Emily Aguilar-Pine; Georgina L. Aitolo; Galen P. Halverson; Brett J. Baker (Proceedings of the National Academy of Sciences, 2026)
Resolving the biological and geological events that led to the origin of eukaryotes is an ongoing challenge in biology. A major step in the evolution of complex cellular life was the merger between an ancestral host cell and a bacterium (that became the mitochondrion) some two billion years ago. Recently, metagenomics has enabled the reconstruction of a broad diversity of genomes, referred to as the Asgard Archaea. The Asgards are monophyletic with eukaryotes on the tree of life. Asgards have an array of genes, previously thought exclusive to eukaryotes, involved in cellular trafficking, the ubiquitin system, endosomal sorting, and cytoskeleton formation, with growing evidence demonstrating the functions of these proteins mirror those in eukaryotes. This gene repertoire suggests that these Archaea are descendants of the archaeal host from which eukaryotes evolved. Increased sampling has revealed that Asgard lineages are metabolically versatile and play key roles in various ecosystems and uncovered evolutionary transitions between Archaea and eukaryotes, such as innovations in eukaryotic defense systems. The positioning of eukaryotes in the Asgards is debated, but eukaryotes appear to branch within the Heimdallarchaeia. Lineages within this group, particularly Hodarchaeales and Kariarchaeaceae, contain a broad repertoire of eukaryote-like traits, including high-energy yielding metabolisms. Observing and studying Asgard interactions with bacterial descendants of mitochondria in a modern setting will transform our understanding of the origin of complex cellular life.